2018
DOI: 10.3892/etm.2018.6594
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA TCONS_00024652 regulates vascular endothelial cell proliferation and angiogenesis via microRNA‑21

Abstract: Acute coronary syndrome caused by the rupture of atherosclerotic plaques is one of the primary causes of major cardiovascular events, and neovascularization within the plaque is closely associated with its stability. Long noncoding RNA (lncRNAs) is a type of noncoding RNA that serves a crucial role in regulating vascular endothelial cells (VECs). The aim of the present study was to investigate the effect of lncRNA TCONS_00024652 on the proliferation and angiogenesis of VECs following stimulation with TNF-α. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Long ncRNAs can act as miR sponges, thereby interfering with regulation of miR targets. We investigated the expression of several long ncRNAs reportedly implicated miR-21 modulation (24)(25)(26)(27)(28). As shown in Fig.…”
Section: Downregulation Of Mir-21 Associated With Reciprocal Changes mentioning
confidence: 99%
“…Long ncRNAs can act as miR sponges, thereby interfering with regulation of miR targets. We investigated the expression of several long ncRNAs reportedly implicated miR-21 modulation (24)(25)(26)(27)(28). As shown in Fig.…”
Section: Downregulation Of Mir-21 Associated With Reciprocal Changes mentioning
confidence: 99%
“…Located on chromosome 17, miRNA-21 is a member of the mitochondrial family subtype, with its own specific promoter 40 . miR-21 participates in the pathological and physiological processes of many diseases, including cardiovascular diseases, in which it prevents post-infarction cardiac insufficiency through targeted regulation 16 and participates in the process of atherosclerosis by mediating signalling 41 . One study reported that high expression of miRNA-21 can promote fibroblast activation and accelerate the progression of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the expression of several long ncRNAs reportedly implicated miR-21 modulation [24][25][26][27][28] . As shown in Figure 2Ci, TALNEC2 was upregulated in T2D-CLI BM-CD34 + cells and respective CCM; TUG1 was decreased in cells and increased in the CCM; MEG3 was not altered; and TCONS was downregulated in CCM.…”
Section: Downregulation Of Mir-21 Associated With Reciprocal Changes mentioning
confidence: 99%
“…TCONS is an endothelium-associated long ncRNA involved in plaque progression. Binding of miR-21 to TCONS reduces its expression and, for this reason, was proposed as potential treatment to improve endothelial dysfunction and plaque stabilization28 .…”
mentioning
confidence: 99%